Collective Action and Community Resilience in Disaster-Prone Regions of Indonesia - Dyah Ayu Suryaningrum (Eastasouth Institute, 2026)
This study examines the influence of collective action and social capital on community resilience in disaster-prone areas in Indonesia. The research adopts a quantitative approach using a cross-sectional survey design. Data were collected from 100 respondents selected from disaster-affected communities and measured using a structured questionnaire based on a five-point Likert scale. The collected data were analyzed using SPSS version 25, employing descriptive statistics, reliability and validity testing, classical assumption tests, and multiple linear regression analysis. The results indicate that both collective action and social capital have a positive and significant effect on community resilience. Social capital shows a stronger influence compared to collective action. The model explains 67.2% of the variance in community resilience, indicating a strong explanatory power. These findings highlight that trust, social networks, and reciprocity play a central role in strengthening community resilience, while collective action further reinforces coordinated community responses during disasters. This study contributes to disaster resilience literature by empirically validating the combined role of social capital and collective action in Indonesian disaster-prone contexts. Practically, the findings suggest that strengthening community networks and participatory disaster preparedness programs is essential for improving resilience capacity.